The performance of polyurethane grout to stabilise hemic peat - Abdurahman, Mohamad Niizar (2020)
Peat has always considered as a challenging ground for any form of construction due to its engineering characteristics such as high short-term settlement, prolonged longterm post construction settlement and high natural moisture content exceedingly more than 100%. Numerous construction materials and methods have been developed in recent years for sustainable construction on peat. The polyurethane (PU) grouting as an option is similar to the cement base grouting application widely used for ground improvement. However, the PU grouting is a strong lightweight material with very short curing time. The Parit Nipah hemic peat has high natural moisture content (> 500%) with high initial void ratio (6.72-10.11) and compression index, cc between 3.17 to 4.57. Optimum mixing ratio for PU of 1:2 (polyol:isocyanate) was established to be used for PU grouting based on its compressive strength (>200 kPa) and curing time (<7 minutes). Numerical analysis was conducted by using PLAXIS 3D Foundation software to determine the boundary for laboratory and field models, as well to determine the grouting depth for PU. The depth of grouting for laboratory scale models were determined at 100 mm and 200 mm, while for the field scale models was at 1 m and 2 m deep. The settlement for natural and treated peat under embankment constructed in stages were monitored. The results of laboratory physical scale models and field models displayed similar settlement pattern. The PU grouted peat showed improvement in term of ground settlement compared to natural peat. PU grouting managed to reduce the settlement of peat up to 30% compared to natural peat. For the PU grouted peat, the increment in term of depth of grouting displayed better settlement improvement. Results showed that PU grouting has good potential to reduce the settlement of hemic peat.